THE ROLE OF CIVIL SOCIETY IN CONFLICT RESOLUTION BETWEEN THE ULFA AND INDIAN - CHANDANA RAJKHOWA (International Journal of Psychosocial Rehabilitation, 2020)
The ULFA (United Liberation Front of Assam) was formed in 1979 with the aim of liberating Assam from the Indian State. The ULA is the most vocal group in Assam that demands secession from the Indian State. In spite of several internal factions in the militant group, ULFA still remains forceful in the state. Efforts have been taken from the state government and civil society organizations to facilitate negotiations between ULFA and the government. In the very initial stage, the civil society groups were very sympathetic to ULFA’s cause and many even supported the militant group. Prior to the deliberation stage, GoI had taken many hard steps to dominate ULFA including use of military and Para military forces. In a state like Assam inclusive dialogue is an efficient method of conflict resolution. The Pro-Talk faction of ULFA has already entered into the formal talks and the Anti-Talk faction is vehemently opposing negotiations with the Government of India (GoI). That’s why internal division between ULFA remains as a strong obstacle in the peace process. This paper will try to evaluate the role of civil society in Assam as a mediator between ULFA and Indian Government.